A very deep Provanna (Gastropoda: Abyssochrysoidea) discovered from the Shinkai Seep Field, Southern Mariana Forearc. (29th November 2016) - Chen, Chong; Watanabe, Hiromi Kayama; Ohara, Yasuhiko
Abstract : The 'Shinkai Seep Field' is a serpentinite-hosted chemosynthetic ecosystem in the Southern Mariana Forearc. In June 2015 the site was revisited and a number of rissoiform gastropods were collected. Taxonomic investigations revealed that these specimens represent a hitherto undescribed species of Provanna (Gastropoda: Abyssochrysoidea), described herein as Provanna cingulata n. sp. This new species is characterized by numerous spiral keels, lack of significant axial sculpture, rounded and inflated whorls, and large size for the genus. With the shell height exceeding 16.5 mm (may reach 20 mm), it is the largest Provanna species known thus far. Phylogenetic analysis using 411 bp of the cytochrome oxidase c subunit I (COI) gene confirmed its systematic placement within the genus Provanna . This is the only gastropod from a family endemic to chemosynthetic ecosystems thus far known from the 'Shinkai Seep Field'. Furthermore, with a collection depth of 5687 m, it represents the deepest known bathymetric range for the superfamily Abyssochrysoidea as a whole.